Operability as an academic subject - Albert A. Abrosimov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Effective work activity requires the maintenance of a high level operability. This skill is among such indexes as thinking, memory and attention, determines the success of an activity. Mechanisms of formation operability, based on nature internals of optimization and adaptation of human body, remain not enough developed. Motivation and interest not always capable of maintaining a high operability. Targets and goals of academic subject are formulated, being aimed at education in methods of maintaining a high level of operability, as a part of increasing efficiency of work activity.